A new analytical model for vibration of a cylindrical shell and cardboard liner with focus on interfacial distributed damping. (15th June 2016) - Plattenburg, Joseph; Dreyer, Jason T.; Singh, Rajendra
Abstract: This paper proposes a new analytical model for a thin cylindrical shell that utilizes a homogeneous cardboard liner to increase modal damping. Such cardboard liners are frequently used as noise and vibration control devices for cylindrical shell-like structures in automotive drive shafts. However, most prior studies on such lined structures have only investigated the associated damping mechanisms in an empirical manner. Only finite element models and experimental methods have been previously used for characterization, whereas no analytical studies have addressed sliding friction interaction at the shell–liner interface. The proposed theory, as an extension of a prior experimental study, uses the Rayleigh–Ritz method and incorporates material structural damping along with frequency-dependent viscous and Coulomb interfacial damping formulations for the shell–liner interaction. Experimental validation of the proposed model, using a thin cylindrical shell with three different cardboard liner thicknesses, is provided to validate the new model, and to characterize the damping parameters. Finally, the model is used to investigate the effect of the liner and the damping parameters on the modal attenuation of the shell vibration, in particular for the higher-order coupled shell modes. Highlights: A new analytical model to characterize the vibration of shell with cardboard liner. Accounts for relative motion between shell/liner (previously absent from literature). Several damping mechanisms are considered (structural, viscous, Coulomb). Experimental validation provided for model. Model is used to study higher-order coupled modes.